Applying and Evaluating Teacher Professional Development Models – A Case Study of a Pakistani School - Sarwat Nauman (International Journal of Experiential Learning & Case Studies, 2017)
There is recently a shift towards competency-based education in Pakistan, which is the outcome of its National Education Policy. This research investigates the professional development activities that teachers embark on related to this change and in turn the extent to which the in-service teacher development taking place in schools of Pakistan. Through a case study approach, this research will investigate one of the best schools of Karachi in terms of its board results and probe to see how a school system encourages its teachers to develop them professionally. It is concluded that three models of teacher development were being followed unintentionally at the school: Individually-Guided Staff Development model, Observation/Assessment model and the Training Model. The problem was that these models were not followed in their full spirit due to lack of motivation from the administration. Even though school systems are trying to professionally develop their teachers, they lack the competency as to how to conduct a successful teacher development program.